2021
DOI: 10.1002/ps.6630
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated CO2 on activities of protective and detoxifying enzymes in Frankliniella occidentalis and F. intonsa under spinetoram stress

Abstract: BACKGROUND Elevated CO2 can directly affect the toxicity of insecticides to insects and the physiological response of insects to insecticides. Frankliniella occidentalis and F. intonsa are highly destructive pests that target horticultural crops. Spinetoram is an effective pesticide against thrips. This study sought to explore the effect of elevated CO2 on efficacy of spinetoram against F. occidentalis and F. intonsa and effect of the spinetoram on activities of protective and detoxifying enzymes under elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In the current study, the decreased susceptibility of F. occidentalis to spinetoram was linked to changes in CarE activity, suggesting that CarE plays a role in the detoxification metabolism of spinetoram. Previous studies showed that spinetoram treatment can increase the activities of CarE in F. occidentalis [37]. However, the precise mechanism by which of spinetoram stress induces increased activity of CarE should be explored further.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the current study, the decreased susceptibility of F. occidentalis to spinetoram was linked to changes in CarE activity, suggesting that CarE plays a role in the detoxification metabolism of spinetoram. Previous studies showed that spinetoram treatment can increase the activities of CarE in F. occidentalis [37]. However, the precise mechanism by which of spinetoram stress induces increased activity of CarE should be explored further.…”
Section: Discussionmentioning
confidence: 94%
“…Carboxylesterase (CarE), glutathione S-transferase (GST), acetylcholinesterase (AChE), and the cytochrome P450 enzyme system (CYP450) are important metabolic detoxifying enzymes found in insects. Detoxification enzymes in insects are induced by various exogenous or endogenous compounds, meaning that insects can quickly adapt to environmental stresses, such as insecticides [33], extreme temperatures [36] and carbon dioxide [37], etc. Research has shown that insecticides have different effects on insect defense enzyme systems, and that the changes in the activity of the enzymes are related to the toxic death of insects or indeed the development of insect resistance.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that pesticide intoxication produces oxidative stress in insects, thus, the organism reacts and metabolizes the pesticide active ingredient, inducing lipid peroxidation (Cui et al, 2017; Hu et al, 2019; Li et al, 2021; Sule et al, 2022; Valeria et al, 2020). Chlorantrailiprole and spinetoram are two of the most used insecticides for controlling C. suppressalis , and high concentrations of ROS can be caused by exposure to the two pesticides (Fan et al, 2022). Our results were consistent with these observations that both two pesticides stimulated the expression of CsPrx5 and CsPrx6 in C. suppressalis , indicating that these two Prxs play a significant role in the antioxidant process.…”
Section: Discussionmentioning
confidence: 99%
“…Due to similar niches, competitive interaction between F. occidentalis and F. intonsa has been frequently reported. It has been reported that the relative abundances between F. occidentalis and F. intonsa varies depending on plant hosts and abiotic conditions [44][45][46][47][48][49]. Our previous study found that species-specific aggregation pheromones regulated by the ratio of pheromone compounds might also contribute to the coexistence of the two thrips species [50].…”
Section: Introductionmentioning
confidence: 94%